Systematic Literature Review: Research on Pencak Silat using Vos Viewers in the Scopus Database for 2018-2022 - Wardoyo, Hendro; Setiakarnawijaya, Yasep (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Pencak silat is a branch of full body contact martial arts which is categorized as a strenuous sport where the body requires quite a lot of energy to produce excellent physical condition in supporting techniques and tactics. This study uses a descriptive quantitative method with a bibliometrics approach. The research data used for scientific journals or articles spanning 2018-2022 is sourced from the Scopus database. A scientific article search was carried out using the Publish or Perish application with the keyword "Pencak Silat" in the article title, category, abstract, keywords. The map for the development of the Pencak Silat scientific publication model was analyzed using the VOSViewer application. From the search results using the Publish or Perish application, with the maximum number of searches used, namely 1000 articles, there were 200 published articles according to the keywords entered, then by type filtering using articles there were 32 papers written in article form. Based on the results and discussion, it can be concluded that there have been increases and decreases in the last 2 years, namely in 2021 there has been a significant increase of 11 articles or 34.4% as the highest number of publications because in 2022 it has decreased with the publication of articles of 9 articles or 28.1%.